Teori Kemaslahatan Sebagai Batasan Judicial Activism Dalam pengujian undang-undang oleh Mahkamah Konstitusi - Alatas, Ali; Zulfickar, Ficky M; Hutabarat, Patio Alfredo Nugraha (Jurnal Konstitusi & Demokrasi, 2024)
In this paper, the concepts of judicial activism and judicial restraint are discussed as the way the Constitutional Court (MK) tests laws against the 1945 Constitution of the Republic of Indonesia (UUD 1945). Active judges can do new things to address legal vacuums or social change, but this can trigger criticism due to the potential for exceeding judicial authority. In contrast, judicial review emphasizes the self-restraint of judges to adhere to the legal text without creating new standards, providing legal stability but considered less responsive in handling complex issues. In addition, as a standard to balance the two approaches, this paper offers a maslahat theory based on Maqashid Syariah. This method centers on the protection of the five main elements of human life: religion, soul, reason, offspring, and property. These values are in line with the values contained in the Pancasila and the 1945 Constitution. By using a benefit-based analysis, the Constitutional Court is expected to make decisions that are substantially fair, maintain differences in power, and meet the needs of society. This paper emphasizes how important it is for Constitutional Court judges to have clear guidelines and to work together with other state institutions to maximize their role as guardians of the constitution.